Dívidas estaduais, federalismo fiscal e desigualdades regionais no Brasil: Percalços no limiar do século XXI - Alexandre Manoe Angelo da Silva; Aristides Monteiro Neto; José Carlos Gerardo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– In this article it is discussed some neglected aspects of Brazilian fiscal federalism related to the costs of debt renegotiation processed in the 1990's. It has been argued there are negative impacts on regional economies that urge to be considered in the present times. Firstly, it is demonstrated that implicit subsidies given by national treasury to the states as a way of putting an end to the rising debts has now benefitted more intensely the strong state economies that the weak ones. The problem with that is the strong state economies are the most indebted ones. Secondly, despite of favoring the strong (more indebted) state economies, it is in the less developed states of federation in which the burden of indebtedness is strong (less subsidies) and in which the public investment efforts are more intense. As an ultimate result, one can affirm that the rules of debt renegotiation, designed and implemented in the 1990's, are now becoming an undesirable mechanism to promote economic regional inequalities.
Keywords: H77; H63; R11; 330; intergovernmental relations; federalism; public debt; regional and local development